Non-conservative Behavior of Dissolved Organic Matter and Trace Metals (Mn, Fe, Ba) Driven by Porewater Exchange in a Subtropical Mangrove-Estuary - Mori, Corinna; Santos, Isaac R.; Brumsack, Hans-Jürgen; Schnetger, Bernhard; Dittmar, Thorsten; Seidel, Michael (Frontiers in Marine Science, 2019)
Estuaries play a key role in controlling the land-ocean fluxes of dissolved organic matter (DOM), nutrients and trace metals. Here, we study how mangrove-fringed areas affect the molecular DOM and trace metal composition in a subtropical estuary. We combined molecular analysis of solid-phase extractable (SPE) DOM using ultrahigh-resolution mass spectrometry with organic and inorganic bulk parameter analyses in surface and porewater along the estuarine gradient of a mangrove-fringed estuary in Australia (Coffs Creek). Statistical analysis and mixing models demonstrate that the fluvial and mangrove-porewater derived DOM and inorganic chemical species were altered and/or removed by the estuarine filter before reaching the coastal ocean. The mangrove-fringed central estuary was a net source for dissolved Mn and Ba as well as total dissolved nitrogen (TDN) and dissolved organic carbon (DOC) to the tidal creek, likely due to the exchange of mangrove-porewater strongly enriched in these constituents. Dissolved Fe was removed from the water column, probably during the tidally driven circulation of creek water through the sulfidic mangrove sediments. In the mangrove-porewater dominated tidal creek, sulfur- and nitrogen-containing as well as aromatic DOM compounds were relatively enriched, whereas phosphorous-containing DOM was relatively depleted compared to non-mangrove fringed areas. In areas with intense mixing of estuarine and marine water masses we observed a strong decrease of these DOM compounds relative to values expected from conservative mixing, suggesting their removal by photodegradation and co-precipitation with particles such as Mn(hydr)oxides and/or as organometallic complexes, leading to more aliphatic DOM signatures at the creek-mouth. Tidally driven porewater exchange and surface water runoff from the mangroves had a stronger effect on the biogeochemical cycling in the estuary than the fluvial input during a dry compared to a wet season. Our study confirms that mangroves can significantly contribute to biogeochemical budgets of (sub)tropical estuaries.